Estilos de aprendizaje y rendimiento académico del área de inglés en alumnos de cuarto grado de secundaria de una institución educativa del Callao - Córdova Maraví, Janet Ignale (2010)
The purpose of this research is to establish the relationship between learning styles and academic achievement in the English area of students in fourth grade of secondary in a Military Educational Institution in Callao. The research design used is a descriptive correlational. The population consists of 217 male students. The instrument used was the Questionnaire of Honey-Alonso of learning styles (CHAEA) and the academic performance of students used the consolidated registers of evaluation of the English area 2009. For the statistical analysis was used the SPSS 15.0, the results indicated a statistically significant association between the theoretical and pragmatic style to the final annual English average.